A területi érdekképviselet, a területi politika és a normatív szabályozás alapkérdései - Csefkó, Ferenc (Tér és Társadalom, 1992)
In the field of regional development, the author gives a short review of the mechanisms of interests which should be taken into consideration in order to make government decisions on concensual basis. After exposing cetain fundamental issues of regional policy, the author makes an account of those corporate systems which can, in principle, play some role in the decision-making processes. Corporate systems at the level of local authorities and the association of settlements are given special emphasis. The law on local authorities allows the local authorities to create different associations. However we have to note, that the settlements have not really used this opportunity during the last one-one and a half years. Instead, the counties were more initiative in many places and fields. Associations covering the whole county, and established by the local authority of a county and the local authorities of the settlements have special role among the associations. Besides others, the aim of these associations is "...the more effective and rational solution of regional problems," "...management of enterprises and ventures, and organization of regional services." In its complexity, this type of association is almost equal to a medium-level of supply and service if it has planning and development tasks as well. Their activities are, at the same time, realized in concrete decisions on regional development. Consequently, the main and the decisive part of the tasks of the associations are found in settlement and regional development. The associations of settlements and the different associations of small regions can join effectively in the formation of regional policy. They are free to practise their rights in legislation, but they can also participate in the elaboration of mechanisms helping the coordination of interests, and in the development of large investment projects, regional programs, etc. Another group of their tasks can be the organization of services, the development of information flow, solution of the conflicts of interests, putting up tenders, supporting the development of international-regional connections. These associations can also collaborate with each other in the elaboration of the tasks of the national economy influencing the region, in decreasing regional differences and the differences in chances and opportunities, extending this way the present means of regional development. The author deals with the counties from the point of view of the corporate system. The law on regional development can, in no way, avoid the problems of the medium level. It cannot be decided as yet, whether the present „floating" counties will survive with their obligation to care about the fundamental services and the maintenance of the institutions; or a „govermental county" will develop; or the counties will strengthen through finding new ways of their own; or the counties will cease to exist as local governmental units, and their roles will be fulfilled by other organizations, offices, institutions at a regional level. Independent from this, regional policy and the law on regional development raise the issue of regional disribution as well, also in respect of the corporate system. The last part of the study lists the most important items of normative regulation. A lot of space is devoted to discuss the necessity of legal legislation, and if they are considered to be necessary, those key issues have to be identified, that can guarantee the birth of an executive and executable norm, which helps, through legal means, the development of a smaller or bigger region, and the improvement of the living conditions of people living there.